Tacrolimus-Associated Dilated Cardiomyopathy in Adult Patient After Orthotopic Liver Transplant - Jennifer McLeod MD; Stephanie Wu MD; Luanda Grazette MD; Anna Sarcon MD (SAGE Publishing, 2017)
This report presents a case of tacrolimus cardiotoxicity in an adult patient who received tacrolimus immunosuppression for orthotopic liver transplant (OLT). Tacrolimus-associated cardiotoxicity has been described in the literature, however this is the first case to document the development of a dilated cardiomyopathy in a patient shortly after initiating tacrolimus therapy post transplant. With the growing use of tacrolimus in transplant medicine, this case report expands the literature of tacrolimus cardiotoxicity and can aid clinicians in the evaluation and management of patients exposed to this form of immunosuppression.